Handbook of Ecomaterials 2017
DOI: 10.1007/978-3-319-48281-1_5-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose: Insight into Health and Medical Applications

Abstract: Discovering biomaterials of renewable and sustainable has become primary goal among researchers as a way to mitigate environmental impact. One of those abundantly present is cellulosic materials. Agricultural waste such as banana rachis, wheat straw, cassava bagasse, and coconut husk have been identified as a reliable resources in the production of cellulose fibers, a natural fillers for composite applications. Due to its high strength and stiffness, biodegradable, and biocompatible, this material has found it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…It is reported that nanocellulose-based systems demonstrated sustained release of the loaded drug, with great biomedical applications [ 31 ]. In addition, nanocellulose can be used in food packaging [ 10 ], tissue engineering [ 32 ], cosmetic additives, medical implants [ 33 ], paper industry [ 34 ], 3D printing [ 35 ], wastewater treatment [ 36 ], biocatalysts [ 37 ], bioenergy [ 38 ](Zhu et al., 2016), wood adhesives, lenses, fingerprint detection [ 30 ](Trache et al., 2020), and textile industries [ 39 ](Forsman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that nanocellulose-based systems demonstrated sustained release of the loaded drug, with great biomedical applications [ 31 ]. In addition, nanocellulose can be used in food packaging [ 10 ], tissue engineering [ 32 ], cosmetic additives, medical implants [ 33 ], paper industry [ 34 ], 3D printing [ 35 ], wastewater treatment [ 36 ], biocatalysts [ 37 ], bioenergy [ 38 ](Zhu et al., 2016), wood adhesives, lenses, fingerprint detection [ 30 ](Trache et al., 2020), and textile industries [ 39 ](Forsman et al., 2017).…”
Section: Introductionmentioning
confidence: 99%